Evaluation and heritability studies of local lima bean (phaseolus lunatus L.) cultivars from South-west Nigeria (2007)
Seven local Lima bean cultivars were evaluated at Ile-Ife in the humid rainforest environment of south western Nigeria for two years. A randomized complete block design with three replications was used each year. Data were subjected to analysis of variance, Pearson correlation and stepwise multiple regression analyses. Heritability estimates of 10 agronomic characters evaluated were also determined. Significant year and cultivar effects were observed for most of the characters. Seed yield ha-1 varied from 289.14 to 1358.74 kg. Only two cultivars had seed yield above 1000 kg ha-1, others yielded poorly. Seed yield had positive and significant correlation with branching height, number of seeds per pod, 100- seed weight and inter-nodal length. Results of stepwise multiple regression analysis showed that pod weight per plant, 100-seed weight and pod length were the main seed yield components in Lima bean and together they accounted for 98% of the variability. One hundred seed weight also had the highest broad sense heritability estimate of 98%. Characters such as pod length, mid leaflet surface area, pod weight per plant and inter-nodal length were moderately heritable. The implications of these findings in lima bean improvement were discussed.